2008
DOI: 10.4103/0970-1591.39549
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ureteral stones: A prospective randomized controlled trial on comparison of Ho:YAG laser and pneumatic lithotripsy

Abstract: Objectives:To study the treatment of ureteric stones by HO:YAG laser lithotripsy and pneumatic lithotripsy and to evaluate the results of the two treatment modalities to assess effectiveness and complications.Materials and Methods:Over 1-year period, a total of 79 patients with 82 ureteral stones were randomized into two groups. In group 1 (39 cases with 41 ureteral stones) ureteroscopic HO:YAG laser lithotripsy was performed using a rigid 8 Fr-ureteroscope (LL group). In group 2 (40 cases with 41 ureteral sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
4
19
0
2
Order By: Relevance
“…2 ). Early Stone-Free Rate Except Cimino et al [12] , Maghsoudi et al [16] and Manohar et al [7] assessing stone-free rate later than 1 month post operation, all the other trials reported information on early stone-free rate. The results showed LL improved an early stone-free rate than PL (OR 2.69, 95% CI 1.91-3.78, p = 0.00001; fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). Early Stone-Free Rate Except Cimino et al [12] , Maghsoudi et al [16] and Manohar et al [7] assessing stone-free rate later than 1 month post operation, all the other trials reported information on early stone-free rate. The results showed LL improved an early stone-free rate than PL (OR 2.69, 95% CI 1.91-3.78, p = 0.00001; fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mean Operative Time All studies, aside from Maghsoudi et al [16] , unequivocally compared the mean operative time. We excluded studies by the Manohar et al [7] , Garg et al [15] and Razzaghi et al [3] because they only counted the lithotripsy time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stone free rate (SFR) was higher in Ho:YAG laser group vs pneumatic lithotripsy (37 cases (90.2%) vs 30 cases (73.20%) (P = 0.46). 32 In another randomized controlled trial, in 2010, Basiri et al studied 100 children with distal ureteral stone, compared transurethral lithotripsy with shock wave lithotripsy (SWL) and holmium laser to evaluate the superior modality. Both were suitable modalities for removal of distal ureteral stone at that age range.…”
Section: Treatment Of Urolithiasis With Lasermentioning
confidence: 99%
“…Ancak, bu durumun yukarıda Maghsoudi ve ark. (15) yaptığı ileri dönük çalışmada, proksimal üreter taşlarında LL yapılan grupta %2,4, PL yapılan grupta %7,3 oranında taş migrasyonu saptanmış, ancak istatistiksel olarak anlamlı fark bulunmamıştır. Çalışmamızda toplam 9 adet taş migrasyonu gözlendi ve hepsi üreter üst uç taşı idi.…”
unclassified